Ribbons of scarlet : a novel of the French Revolution's women - Quinn, Kate; Dray, Stephanie; Kamoie, Laura Croghan; Perinot, Sophie; Webb, Heather, 1976 December 30-; Knight, Eliza (William Morrow, an imprint of HarperCollinsPublishers, 2019)
In late eighteenth-century France, women do not have a place in politics. But as the tide of revolution rises, women from gilded salons to the streets of Paris decide otherwise<U+2014>upending a world order that has long oppressed them. Blue-blooded Sophie de Grouchy believes in democracy, education, and equal rights for women, and marries the only man in Paris who agrees. Emboldened to fight the injustices of King Louis XVI, Sophie aims to prove that an educated populace can govern itself--but one of her students, fruit-seller Louise Audu, is hungrier for bread and vengeance than learning. When the Bastille falls and Louise leads a women<U+2019>s march to Versailles, the monarchy is forced to bend, but not without a fight. The king<U+2019>s pious sister Princess Elisabeth takes a stand to defend her brother, spirit her family to safety, and restore the old order, even at the risk of her head. But when fanatics use the newspapers to twist the revolution<U+2019>s ideals into a new tyranny, even the women who toppled the monarchy are threatened by the guillotine. Putting her faith in the pen, brilliant political wife Manon Roland tries to write a way out of France<U+2019>s blood-soaked Reign of Terror while pike-bearing Pauline Leon and steely Charlotte Corday embrace violence as the only way to save the nation. With justice corrupted by revenge, all the women must make impossible choices to survive--unless unlikely heroine and courtesan<U+2019>s daughter Emilie de Sainte-Amaranthe can sway the man who controls France<U+2019>s fate: the fearsome Robespierre.